2018
DOI: 10.1016/j.kint.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The elevation of circulating fibroblast growth factor 23 without kidney disease does not increase cardiovascular disease risk

Abstract: High circulating fibroblast growth factor 23 (FGF23) levels are probably a major risk factor for cardiovascular disease in chronic kidney disease. FGF23 interacts with the receptor FGFR4 in cardiomyocytes inducing left ventricular hypertrophy. Moreover, in the liver FGF23 via FGFR4 increases the risk of inflammation which is also found in chronic kidney disease. In contrast, X-linked hypophosphatemia is characterized by high FGF23 circulating levels due to loss of function mutations of the phosphate-regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 50 publications
4
57
1
1
Order By: Relevance
“…Our data are in line with recent experimental findings also challenging FGF23's role in myocardial disease, e.g. primary elevations of FGF23 were found to be innocent and harmless to the rodent heart . Such data call into question the direction of causality and underline speculations that actually heart disease per se contributes to elevated FGF23 levels (pointing towards reverse causality) .…”
Section: Discussionsupporting
confidence: 91%
“…Our data are in line with recent experimental findings also challenging FGF23's role in myocardial disease, e.g. primary elevations of FGF23 were found to be innocent and harmless to the rodent heart . Such data call into question the direction of causality and underline speculations that actually heart disease per se contributes to elevated FGF23 levels (pointing towards reverse causality) .…”
Section: Discussionsupporting
confidence: 91%
“…Despite this early enthusiasm for such novel therapeutic interventions, certain caveats have recently arisen: Experimentally, independent study groups did not unanimously confirm a cardiotoxic effect of FGF23 [15][16][17][18][19], and latest rodent studies have implied that FGF23 may be a consequence rather than a cause of myocardial disease [20]. Epidemiologically, the majority of cohort studies that suggested an independent role of plasma FGF23 to predict adverse cardiovascular outcome dates back several years [3][4][5]7], when our understanding of FGF23 regulation was less comprehensive.…”
Section: Strength Of Fibroblast Growth Factor 23 As a Cardiovascular mentioning
confidence: 99%
“…To address the first of these 2 questions, Pastor-Arroyo and colleagues 8 analyzed the cardiac phenotype in a mouse model of X-linked hypophosphatemia (XLH). As the most common form of inherited rickets, XLH is caused by mutations in the phosphate-regulating gene with homologies to endopeptidase on the X chromosome (PHEX), which causes an increase in the production and secretion of intact FGF23 from bone, which in turn decreases renal phosphate reabsorption resulting in hypophosphatemia.…”
mentioning
confidence: 99%
“…4,5 However, these mice also show hypertension and an approximately 20-fold elevation of serum FGF23 levels, which is different from Phex C733R mice that are normotensive and have FGF23 elevations of about 10-fold. 8 Surprisingly, a recent phenotypic analysis of the Hyp mouse model revealed the absence of cardiac hypertrophy. 11 However, because this study does not report serum FGF23 levels and mice were normotensive, it is difficult to compare its outcome with findings from previous studies.…”
mentioning
confidence: 99%